Edutainment Approach to Teaching Verbs: A Battle-Themed English Lesson - Sanriomi Sintaro (CHAIN: Journal of Computer Technology, Computer Engineering, and Informatics, 2025)
English is the primary foreign language that plays a crucial role in various aspects of life, particularly in accessing global information, mastering, and developing knowledge across multiple fields, including technology, arts, and culture. But not only that, English is also included as one of the subjects in the world of education in Indonesia. Furthermore, English proficiency significantly contributes to establishing and strengthening relationships with different nations worldwide, whether in academic, professional, or social contexts.With the rapid advancement of technology and the declining motivation of students in learning, it is increasingly important to implement more innovative and modern learning approaches. One such approach is edutainment, which integrates educational content with entertainment elements to enhance student engagement and create a more effective learning experience. Additionally, competition-based methods can serve as an alternative reference in the development of edutainment to further stimulate students' interest in learning. This study focuses on developing competition or battle-themed edutainment as a medium for introducing verbs in English, along with their past tense (V2) and past participle (V3) forms. Battle-based edutainment has proven to be an effective learning tool. Based on tests conducted on 30 target users, their satisfaction levels were measured using the SUS Score, which resulted in an average score of 89.25, classified within the A scale, indicating an above-average satisfaction level.